Site-specific integration of the temperate bacteriophage phi adh into the Lactobacillus gasseri chromosome and molecular characterization of the phage (attP) and bacterial (attB) attachment sites. - Raya, R R (1992)
The temperate bacteriophage phi adh integrates its genome into the chromosomal DNA of Lactobacillus gasseri ADH by a site-specific recombination process. Southern hybridization analysis of BclI-digested genomic DNA from six relysogenized derivatives of the prophage-cured strain NCK102 displayed phage-chromosomal junction fragments identical to those of the lysogenic parent. The phi adh attachment site sequence, attP, was located within a 365-bp EcoRI-HindIII fragment of phage phi adh. This fragment was cloned and sequenced. DNA sequence analysis revealed striking features common to the attachment sites of other site-specific recombination systems: five direct repeats of the sequence TGTCCCTTTT(C/T) and a 14-bp inverted repeat. Oligonucleotides derived from the sequence of the attP-containing fragment enabled us to amplify predicted junction fragment sequences and thus to identify attL, attR, and attB. The core region was defined as the 16-bp sequence TACACTTCTTAGGAGG. Phage-encoded functions essential for site-specific insertion of phage phi adh were located in a 4.5-kb BclI fragment. This fragment was cloned in plasmid pSA34 to generate the insertional vector pTRK182. Plasmid pTRK182 was introduced into L. gasseri NCK102 by electroporation. Hybridization analysis showed that a single copy of pTRK182 had integrated at the attB site of the NCK102 erythromycin-resistant transformants. This is the first site-specific recombination system described in lactobacilli, as well as the first attP-based site-specific integration vector constructed for L. gasseri ADH.